ZAYD B. THABIT R.A. DAN PENDIRIANNYA DALAM KES-KES FARA'ID TERTENTU - Mahad Musa, Zahari (Jurnal Syariah, 2019)
Qawl al-.$abiibi, a disputed source of Islamic law among Muslim juristsJunctions at explaining the rulings based on independent legal reasoning (ijtihad) of Prophet Muhammad's (p.b.u.h,) companions. This is due to the fact that the companions are those who belong to the early generations who witnessed the gradual process of revelation onto Prophet Muhammad (p.b.u.h,) apart from being the first recipients of Islamic teachings. However. the authoritative legal reasoning is very much focused on only a few number of distinguished companions, specifically those who were frequently referred to by others. In this aspect, one should not forget Zayd b. Thiibit r.a, a personality with acknowledged credibility and expertise. Thus, this paper aims to identify this outstanding gift of deriving ijtihad by Zayd b. Thiibit r.a. as a sample of qawl al-.$abiibl. Apart from that, this paper also aims at proving the expertise ofZayd b. Thiibit r.a. in fara'id as recognized by Prophet Muhammad (p.b.u.h,) in one of His (p.b.ii.h,) hadiths. The discussion will also deal with certain leading and known faraid cases with distinctive calculative methods.